1982
DOI: 10.2134/agronj1982.00021962007400050034x
|View full text |Cite
|
Sign up to set email alerts
|

Warm‐season Grass Establishment with Atrazine1

Abstract: Weed competition is a limiting factor in warm‐season grass establishment often delaying the first forage harvest 2 or 3 years. Weed control with herbicides could reduce this competition resulting in more rapid grass establishment. Field experiments were conducted to evaluate the effect of atrazine [2‐chloro‐4‐(ethylamino)‐6‐(isopropylamino)‐s‐triazine] on weed control, warm‐season grass establishment, and forage yield during the seeding and following year. Several warm‐season grass species were spring seeded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
3

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 9 publications
4
54
0
3
Order By: Relevance
“…Atrazine has improved switchgrass establishment by controlling broadleaf weeds and C 3 (cool season) weedy grasses [1,5], but it has limited effectiveness for controlling warm-season annual grasses such as foxtails (Setaria spp.). Previous unpublished herbicide screening research by USDA-ARS in Lincoln, NE indicated that switchgrass establishment was improved by imazapic (Plateau \ ) application at 35 g a.i.…”
Section: Introductionmentioning
confidence: 99%
“…Atrazine has improved switchgrass establishment by controlling broadleaf weeds and C 3 (cool season) weedy grasses [1,5], but it has limited effectiveness for controlling warm-season annual grasses such as foxtails (Setaria spp.). Previous unpublished herbicide screening research by USDA-ARS in Lincoln, NE indicated that switchgrass establishment was improved by imazapic (Plateau \ ) application at 35 g a.i.…”
Section: Introductionmentioning
confidence: 99%
“…Martin and Moomaw (1974) report excellent control of bluegrass from applications of 2 lb/a (2.24 kg/ha) glyphosate in spring while warm season grasses were dormant. Waller and Schmidt (1983) report significant decreases in the productivity of Poa pratensis along with increasing big bluestem production as a result of April 21 applications of 1 lb/a (1.12 kg ha) glyphosate on Poa-infested loams in southeastern Nebraska.…”
Section: Management/monitoring Management Requirementsmentioning
confidence: 95%
“…Sources: Martin et al 1982;Muir et al 2001;Vogel et al 2001;Vogel et al 2002;Hanson et al 2005;Fike et al 2006;Mulkey et al 2006;Cramer et al 2007;Lee et al 2007;Mitchell et al 2008;Mitchell et al 2012;NRDC 2014.…”
Section: Rotation Cycle Readings On Ph Soil Nutrient Content Testunclassified